CERTAINTY OF RESPONSE INDEX (CRI): MISKONSEPSI SISWA SMP PADA MATERI PECAHAN - Siti Ulfah; Harina Fitriyani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Thisreason of this research is most of the students still have difficulties in understanding the concept of fraction. The purpose of this research is to determine the misconception of students using the Certainty of Response Index (CRI) method and the cause of the misconception. Method of this research is descriptive qualitative. Subjects in this research were 27 students of VIIG class at SMP Muhammadiyah 1 Yogyakarta in academic year 2016/2017. The research data were obtained from test instrument which multiple choice te using CRI technique to identify student misconception and interview withstudents. Data analysis techniques using Miles and Huberman model, that is data reduction, data presentation, and conclusion.The results showed that 28.89% of studentswho experienced misconception. The location of misconceptions experienced by students occurs in the concept of the relationship between two fractions, changing the fractional shapes, fractions of rank, the multiplication and meaning of the word "of", addition, and division. Misconceptions experienced by students were caused by preconception (initial concept), incomplete or wrong reasoning, false intuition, and student ability.Keywords: Misconception, Certainty of Response Index (CRI), Fraction.